Pengaruh Tinggi Bukaan Katup terhadap Torsi dan Daya pada Motor Besin 4 Langkah Berkapasitas 200CC - Dadang Andi Saputra; Purwoko Purwoko (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Automobiles are now the primary mode of transportation due to rapid technological advancements. One method for accomplishing ideal volumetric effectiveness and augment power is to change the camshaft. This study means to grow understanding in the auto world in regards to power and force and to assess the impact of changes in camshaft lift level on a 200cc limit bike utilizing pertalite fuel. The information from the review is introduced in tables and examined utilizing the two-way ANOVA technique and charts. The results of the analysis indicate that a comparison of the power data obtained by adding the lift height (test 3) yields a result of 16 66 HP at 8500 RPM. In the mean time, the force information demonstrates the way that the force examination of the three tests can be supposed to be the most elevated information of the three tests, to be specific (test 3) which is completed by adding a high lift to get a force of 17 59 Nm at engine rotation 5000 RPM. Utilized DeepL.com (free version) for translation.